New Virgulid Cercaria (Trematoda, Lecithodendroidea) from Freshwater Mollusk Melanopsis praemorsa (Melanopsidae) from Azerbaijan Water Bodies. Morphology of Cercaria agstaphensis 27 - Manafov, A.A. (Вестник зоологии, 2011)
Illustrated morphological description and differential diagnosis of a new virgulid cercaria, Cercaria agstaphensis 27, from the freshwater prosobranchial mollusk Melanopsis praemorsa (Linneus, 1758) are given. Special attention is paid to the arming of tegument, the structure of glandular apparatus, excretory system, digestive system and other individual morphological characters important for taxonomy.